A bola da vez: gestão e resistência no cotidiano de uma favela carioca em contexto de pacificação - Postigo, Evelyn Louyse Godoy (2014)
Rio de Janeiro city has undergone significant changes over the past two decades, principally respect to devices that regulates the way of life from populations from favelas' neighborhood. They explain that the conflict in the relation favela and asphalt has been increasingly understood by the violence key. I noteworthy which these changes have been with marked with the preparation of the city for the mega events Soccer World Cup and Olympic Games. In view of this scenery, the aim of this work was to think, starting from a ethnographic research performed in Cidade de Deus Rio de Janeiro (one of the first slum to receive the project Unidade de Polícia Pacificadora UPP [Pacifying Police Unit]), how social and politic conflicts are daily experienced by favela dwellers under pacification context. I argued that, if in the ambit of production of discourses, the spheres of politics, religion, State and crime can be antagonistic and in conflict. At the level of social relations more capillaries, the borders between these spheres are blurred. It is intended to, but they are not exclusionary among them, coexisting within assessed sceneries.